Emerging applications of cancer bacteriotherapy towards treatment of pancreatic cancer - Henderson, Emily A.; Lukomski, Slawomir; Boone, Brian A. (Frontiers in Oncology, 2023)
Pancreatic cancer is a highly aggressive form of cancer with a five-year survival rate of only ten percent. Pancreatic ductal adenocarcinoma (PDAC) accounts for ninety percent of those cases. PDAC is associated with a dense stroma that confers resistance to current treatment modalities. Increasing resistance to cancer treatments poses a challenge and a need for alternative therapies. Bacterial mediated cancer therapies were proposed in the late 1800s by Dr. William Coley when he injected osteosarcoma patients with live streptococci or a fabrication of heat-killed Streptococcus pyogenes and Serratia marcescens known as Coley’s toxin. Since then, several bacteria have gained recognition for possible roles in potentiating treatment response, enhancing anti-tumor immunity, and alleviating adverse effects to standard treatment options. This review highlights key bacterial mechanisms and structures that promote anti-tumor immunity, challenges and risks associated with bacterial mediated cancer therapies, and applications and opportunities for use in PDAC management.